Analyzing the global political economy - Walter, Andrew; Sen, Gautam (Princeton University Press, 2008)
Ideally suited to upper-undergraduate and graduate students, Analyzing the Global Political Economy critically assesses the convergence between IPE, comparative political economy, and economics. Andrew Walter and Gautam Sen show that a careful engagement with economics is essential for understanding both contemporary IPE and for analyzing the global political economy. The authors also argue that the deployment of more advanced economic theories should not detract from the continuing importance for IPE of key concepts from political science and international relations. IPE students with little or no background in economics will therefore find this book useful, and economics students interested in political economy will be alerted to the comparative strengths of political science and other social science disciplines. A concise look at the foundations of analysis in the political economy of global trade, money, finance, and investment Suitable for upper-undergraduate and graduate students with some or no economic background Techniques and findings from a range of academic disciplines, including international relations, political science, economics, sociology, and history Further reading and useful weblinks including a range of relevant data sources, listed in each chapter